Pedagogical, Professional, and Resource Concerns: Understanding Pre-service Teachers' Preparedness for Inclusive Education Implementation - Dr. Yasira Waqar; Dr. Tanzeela Urooj; Dr. Faisal Anis; Dr. Yaar Muhammad (Research Journal of Psychology, 2025)
The focus of this study was to explore the underlying factor structure of pre-service teachers’ concerns related to their implementation of inclusive education. In the Pakistani context, limited research exists on pre-service teachers’ concerns regarding preparedness for inclusive education implementation, while education around the world is gaining increasing prominence in inclusive education. A quantitative approach to data collection was adopted from the pre-service teachers (N=635) from five Pakistani universities using a thirty-item questionnaire. The dimensionality of teachers’ concerns was examined using exploratory factor analysis (EFA) with Oblimin rotation. Bartlett’s test (p < .001) and the Kaiser-Meyer-Olkin measure (.938) indicated sampling adequacy. The EFA revealed a three-factor structure explaining 52.77% of the total variance: Pedagogical Preparedness concerns (10 items, variance=18.76%), Professional Efficacy concerns (10 items, variance=17.72%), and Resource and Support Concerns (10 items, variance=16.31%). There was strong internal consistency among all factors (Cronbach’s α .898 to .903). Intercorrelations among factors were extremely low (.009-.072), indicating distinct dimensions. The results suggest that pre-service teachers’ concerns with inclusive education occur along the dimensions of pedagogic skills, competency to deliver inclusive education, pre-service teachers’ professional development needs, and the provision of institutional support. The results of this study give good insights into teacher education programs in Pakistan in terms of targeted interventions in these three areas. The empirically validated factor structure of the survey provides a framework for the study of concerns among pre-service teachers with respect to the implementation of inclusive education. The relationship of these factors with actual teaching performance and student outcomes in inclusive settings is important for future research.